2018
DOI: 10.1080/17470218.2017.1371780
|View full text |Cite
|
Sign up to set email alerts
|

Breaking magic: Foreign language suppresses superstition

Abstract: In three studies we found that reading information in a foreign language can suppress common superstitious beliefs. Participants read scenarios either in their native or a foreign language. In each scenario, participants were asked to imagine performing an action (e.g., submitting a job application) under a superstitious circumstance (e.g., broken mirror; four-leaf clover) and to rate how they would feel. Overall, foreign language prompted less negative feelings towards bad-luck scenarios, less positive feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 53 publications
3
31
1
Order By: Relevance
“…The foreign language effect constitutes a positive effect of foreign language use on the promotion of rational decisions. Extant cognitive-psychological studies demonstrated that people who process information in a foreign language are less superstitious (Hadjichristidis et al 2017a), show higher levels of self-regulation (Klesse et al 2015), and-most importantly for our study-are less loss-and risk-averse (Hadjichristidis et al 2017b).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The foreign language effect constitutes a positive effect of foreign language use on the promotion of rational decisions. Extant cognitive-psychological studies demonstrated that people who process information in a foreign language are less superstitious (Hadjichristidis et al 2017a), show higher levels of self-regulation (Klesse et al 2015), and-most importantly for our study-are less loss-and risk-averse (Hadjichristidis et al 2017b).…”
Section: Introductionsupporting
confidence: 53%
“…However, psychological studies suggest that these emotionality levels are sufficient to elicit foreign language effect. For example, Hadjichristidis et al (2017a) scrutinized superstitious beliefs and indicated a strong foreign language effect for participants in bad-luck scenarios, who provided values below 3 on a 9-point scale for their feelings (Study 2 and 3). Moreover, the foreign language effect emerged in the context of risk-taking without real payments as well (e.g., Study 2 of Keysar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a medium effect size for the hypothesised interaction of microaggressions x minority status on global life satisfaction, and using the following parameters -effect size (f) = .30, α = .05, power = .80 -it was found that 90 participants would be sufficient for adequate power. These power calculations were based on assumptions used in a large volume of research across a variety of disciplines, including social psychology, that reached the similar conclusions concerning the number of participants required to find the hypothesised interaction effect (see, e.g., Dowd et al, 2014;Gothe & McAuley, 2016;Hadjichristidis, Geipel, & Surian, 2017;Mackillop, Goldenson, Kirkpatrick, & Leventhal, 2018;Tipler & Ruscher, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps an understanding of Dual-Process models enriches understanding of these concepts, but we think the main ideas we want to discuss can be covered without layering a third construct in between nudges and the FLE for the purposes of this paper. been shown to reduce superstitious beliefs (Hadjichristidis et al, 2019b). Participants who considered events in their non-native language were less likely to attribute negative feelings to "bad luck" events (e.g., breaking a mirror) and less positive feelings toward "good luck" events (e.g., finding a four-leaf clover).…”
Section: Foreign-language Effectmentioning
confidence: 99%